Jigsaw method in reading comprehension - Elfrida BR Silalahi (Universitas Merdeka Malang, 2019)
This study deals with the use of jigsaw method in improving students’ reading at the VIII Grade Students of junior high school PGRI 4 Medan 2017/2018. This research was conducted by applying the Experimental method. The population of this study was the students of the VIII grade of junior high school PGRI 4 Medan. There were four classes which students were 30 in each classes. Totally 120 students. The sample was 60 students in which determined by purposive sampling technique that divided into two (2) groups, (CG) control group and (EG) experimental group. Data was analyzed by t-test formula and used observation sheet and interview sheet to show the result of the process in teaching reading. The result is the data by using t-test found that t-observed (4,8) t-table ( 2,00) with stage of freedom (df) is 58 and standard sense (0,05). And the end of the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. In make yield means jigsaw significantly increasing reading at the VIII neap tide students of junior high school PGRI 4 Medan.